Late Work in Sweden: Exit Pathways Express Unequal Exclusion Risks - Öylü, Gülin; Kelfve, Susanne; Motel-Klingebiel, Andreas (Nordic Journal of Working Life Studies, 2022)
Based on Swedish National Registry Data, this paper investigates the social structure of exclusion risks in late working life in Sweden by analyzing exit from working life, employment breaks, and late employment trajectories according to gender and education. Individuals born in 1950 (n = 107,830) are followed between the years 2010 and 2018. Results show that women with low education exit working life earlier and have a higher risk of employment breaks due to reduced working ability, while men with low education have a higher risk of employment breaks due to unemployment. Men in general and people with high education have a higher probability of moving to self-employment in late working life. We conclude that research and social policies require an understanding of multifarious late work trajectories to unearth the inequality of exclusion risks in the late phases of working life and the potential for interventions towards equal and inclusive prolongation.